Nucleoside Diphosphate Kinases (ndk) reveals a key role in adhesion and virulence of Aeromonas veronii. (December 2020) - Zhang, Lei; Song, Mingfang; Yang, Nuo; Zhang, XiuWen; Abbas Raza, Sayed Haidar; Jia, Kaixiang; Tian, Jiaxin; Zhang, Yang; Zhang, Dongxing; Shi, Qiumei; Wu, Tonglei; Kang, Yuanhuan; et al.
Abstract: Aeromous veronii is a severe pathogen that can infect aquatic organisms and mammals also causes irreparable damage to fish aquaculture. Analysis of the results of epidemiological investigations have revealed that its tolerance to drugs and the virulence of A. veronii have increased in recent years. Most of the researches on A. veronii focuse on the strain isolation, identification, and drug susceptibility. However, we do not know so much about the molecular mechanism of the pathogenesis on A. veronii . Here we identified and obtained the highly expressed TH0426 Nucleoside Diphosphate Kinases ( NDK ) of A. veronii . We first constructed a mutant strain (△- ndk ) by generating an in-frame deletion of the ndk gene, to investigate the functional role in A. veronii TH0426. The ability in the adhesion and invasion of EPC cells and biofilm formation significantly reduced of the △- ndk strain. The motility test showed that the ndk gene affected on the swimming ability, while did not affect the swarming motility. Compared with the wild-type strain TH0426, the pathogenicity of △- ndk strain to zebrafish reduced severely. Besides, the ndk gene has affected the apoptosis rate of A. veronii TH0426. These results would help to demonstrate the function of ndk further and realize the pathogenesis on A. veronii . Highlights: The function controlled by the  ndk  gene was first validated in  Aeromonas veronii. The ability of biofilm formation, the adhesion and invasion to EPC cells significantly decreased for the mutant strain (△- ndk ). Ndk  gene has affected the virulence and apoptosis rate of  A. veronii  TH0426.